A re-evaluation of a fractured carbonate reservoir from the Perth Basin, Western Australia. Issue 1 (1st December 2019) - Ridha Adhari, Muhammad; Wilson, Moyra E.J.; George, Annette D.
Summary: This ongoing research evaluates a fractured carbonate reservoir in the Beekeeper Formation, Perth Basin, focused mainly on the Woodada Field. Previous reports identified a fractured carbonate system as the main hydrocarbon reservoir in the Woodada Field, yet there is no published detailed documentation of reservoir development. The aim of this research is to evaluate the depositional and diagenetic characteristics of the Beekeeper Formation, its fracture system development and their combined impacts on carbonate reservoir quality. This study employs multi-method geological analyses. Subsurface core description, standard microscopy, and acetate peel analyses have been conducted, while scanning electron microscopy, cathodoluminescence petrography, stable isotope geochemistry and fluid inclusion analyses are planned for the coming months. Preliminary results show that the carbonate of the Beekeeper Formation consists of packstone, rudstone, packstone-rudstone, floatstone-packstone and packstone-grainstone. The development of the Beekeeper Formation was affected by tectonic activity. The level of influence of tectonic processes, versus diagenesis and primary sedimentary facies on the development of fracture systems, pore system generation and reservoir quality is still being studied in detail. It is anticipated that this ongoing study will increase our understanding of the Woodada Gas Field and fractured carbonate plays in general.